Globular cluster candidates within the Fornax Cluster: Intracluster globulars? - Bassino, Lilia Patricia (2003)
We present the results of a search for globular clusters in the surroundings of 15 low surface brightness dwarf galaxies belonging to the Fornax Cluster, which was carried out on CCD images obtained with the C and T1 filters of the Washington photometric system. The globular cluster candidates show an extended and probably bimodal (C - T1) color distribution, which is inconsistent with the presence of a single population of metal-poor clusters detected in several dwarf galaxies. The surface number density of these candidates shows no concentration towards the respective dwarf galaxies, in whose outskirts they have been identified. On the contrary, if we split the candidates in two groups according to their projected distances to the center of the Fornax Cluster, those located closer to the center show a higher projected density than those located farther from it. These results suggest that the potential globular clusters might not be bound to the dwarf galaxies. Alternatively, these globulars could form part of the very peripheral regions of NGC 1399 (the central galaxy of the Fornax Cluster) or even belong to the intracluster medium.